Salivary flow rate and oral health status in type 2 diabetics - Cicmil Ana; Govedarica Olivera; Lečić Jelena; Puhalo-Sladoje Dragana; Lukić Ružica; Cicmil Smiljka; Čakić Saša (Serbian Medical Society - Dental Section, Belgrade, 2020)
Introduction Decreased salivary flow is frequently associated with numerous diseases such as diabetes mellitus and may lead to numerous oral diseases. The aim of this study was to compare salivary flow rate and oral health status in type 2 diabetics and healthy controls. Material and methods the study involved 90 patients, divided into the three groups: 30 with well controlled (HbA1c<9%), 30 will poorly controlled (HbA1c≥9%) diabetes and 30 healthy subjects. The following clinical parameters were determined: decayed, missing and filled teeth (DMFT); plaque index (PI), sulcus bleeding index (SBI), probing pocket depth (PPD) and clinical attachment level (CAL). Culture of Candida spp. specimens were obtained from tongue dorsum and inoculated into Sabouraud Dextrose Agar. Saliva was collected using "a spit technique". Results Highest mean of unstimulated salivary flow was in healthy subjects; however significant difference between groups was not observed. Stimulated salivary flow results indicate significant reduction in diabetics as well as significant relation between metabolic control and salivary flow. Unstimulated and stimulated salivary flows were negatively and significantly correlated with periodontal parameters and DMFT. Conclusion the present findings indicate that decreased salivary flow rate could have a significant impact on oral health status in type 2 diabetics.